Agribisnis Kakao dan Produk Olahannya berkaitan dengan Kebijakatan Tarif Pajak di Indonesia - Maswadi Maswadi (Fakultas Pertanian Universitas Tanjungpura, 2011)
One of the policies that impact perceived economic actors in Indonesia, especially in the plantation agriculture sector is the policy of fiscal policy determination of the Value Added Tax of 10% of local transactions, especially cocoa beans and cocoa export tax exemption to foreign countries, processed cocoa export tax by 30% and processed cocoa import tax of 5%. Assessment is made ??considering one of the driving factors is the dominant market of cocoa beans is the overseas market. It can spur international trade, especially cocoa products which will increase foreign exchange, can also be a source of employment especially in the country and also increase the income of the people (farmers and businessmen) who are involved in agribusiness cocoa. However, the impact of this policy will be re-perceived economic actors involved in agribusiness cocoa if cacao products from Indonesia to compete in international markets